IDENTIFICATION OF HOTEL ROOM NEEDS IN CREATING GUEST SATISFACTION AND SUSTAINABLE MANAGEMENT - Fitri Dwi Kusumawati; Agung Sulistyo; Yuli Arisanti (Universitas Nusa Cendana, 2025)
The role of tourism is to change negative feelings into positive ones. Various activities carried out by tourists must lead to satisfaction and comfort. One business that plays an important role in supporting tourism is the hotel industry. The hotel industry offers a wide range of facilities and attractions to ensure guest satisfaction. However, some hotel guests experience dissatisfaction. Several technical problems become negative assessments from guests. This study identifies the need for hotel rooms to support guest activities and create sustainable management. Exploratory qualitative design is combined with triangulation, observation, and interviews. The focus of the study is directed toward the needs of guest accommodation services. This study uses several samples of comments from various media platforms, filtered through the keyword